The Legal Regime of the Mediation Contract - IGNAT, Claudiu (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).06, 2019)
The legal relationships between the parties in mediation, both between the mediators and the parties, as well as between the parties, are established and defined by the mediation contract. The mediation contract is the will agreement of all parties involved in the mediation procedure, without which mediation cannot take place.